Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Endemic and cosmopolitan fungal taxa exhibit differential abundances in total and active communities of Antarctic soils - Filipa Cox; Kevin K. Newsham; Clare H. Robinson (Environmental Microbiology, 2019)
Summary Our understanding of the diversity and community dynamics of soil fungi has increased greatly through the use of DNA‐based identification. Community characterization of metabolically active communities via RNA sequencing has previously revealed differences between ‘active’ and ‘total’ fungal communities, which may be influenced by the persistence of DNA from nonactive components. However, it is not known how fungal traits influence their prevalence in these contrasting community profiles. In this study, we coextracted DNA and RNA from soil collected from three Antarctic islands to test for differences between total and active soil fungal communities. By matching these geographically isolated fungi against a global dataset of soil fungi, we show that widely dispersed taxa are often more abundant in the total community, whilst taxa restricted to Antarctica are more likely to have higher abundance in the active community. In addition, we find that active communities have lower richness, and show a reduction in the abundance of the most dominant fungi, whilst there are consistent differences in the abundances of certain taxonomic groups between the total and active communities. These results suggest that the views of soil fungal communities offered by DNA‐ and RNA‐based characterization differ in predictable ways.

Not poles apart: Antarctic soil fungal communities show similarities to those of the distant Arctic - Filipa Cox; Kevin K. Newsham; Roland Bol; Jennifer A. J. Dungait; Clare H. Robinson (Ecology Letters, 2016)
Antarctica's extreme environment and geographical isolation offers a useful platform for testing the relative roles of environmental selection and dispersal barriers influencing fungal communities. The former process should lead to convergence in community composition with other cold environments, such as those in the Arctic. Alternatively, dispersal limitations should minimise similarity between Antarctica and distant northern landmasses. Using high‐throughput sequencing, we show that Antarctica shares significantly more fungi with the Arctic, and more fungi display a bipolar distribution, than would be expected in the absence of environmental filtering. In contrast to temperate and tropical regions, there is relatively little endemism, and a strongly bimodal distribution of range sizes. Increasing southerly latitude is associated with lower endemism and communities increasingly dominated by fungi with widespread ranges. These results suggest that micro‐organisms with well‐developed dispersal capabilities can inhabit opposite poles of the Earth, and dominate extreme environments over specialised local species.

Nitrogen availability is a primary determinant of conifer mycorrhizas across complex environmental gradients - Filipa Cox; Nadia Barsoum; Erik A. Lilleskov; Martin I. Bidartondo (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1103–1113 Abstract Global environmental change has serious implications for functional biodiversity in temperate and boreal forests. Trees depend on mycorrhizal fungi for nutrient uptake, but predicted increases in nitrogen availability may alter fungal communities. To address a knowledge gap regarding the effects of nitrogen availability on mycorrhizal communities at large scales, we examine the relationship between nitrogen and ectomycorrhizas in part of a European biomonitoring network of pine forest plots. Our analyses show that increased nitrogen reduces fungal diversity and causes shifts in mycorrhizal community composition across plots, but we do not find strong evidence that within‐plot differences in nitrogen availability affect ectomycorrhizal communities. We also carry out exploratory analyses to determine the relative importance of other environmental variables in structuring mycorrhizal communities, and discuss the potential use of indicator species to predict nitrogen‐induced shifts in fungal communities.